2020
DOI: 10.1016/j.clml.2020.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Durable Survival Outcomes in Primary and Secondary Central Nervous System Lymphoma After High-dose Chemotherapy and Autologous Stem Cell Transplantation Using a Thiotepa, Busulfan, and Cyclophosphamide Conditioning Regimen

Abstract: MicroAbstractWe retrospectively analyzed 48 CNS lymphoma patients who received HDC/ASCT using TBC conditioning. We found a 2-year PFS and OS rate of 80.5% and 80.1%, respectively. Toxicities included nausea/vomiting, diarrhea, mucositis, and febrile neutropenia. Treatment-related mortality was 8.3% in the first 100 days post-transplant. This data supports the use of consolidative ASCT in PCNSL and secondary CNS lymphoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Recently, the usefulness of conditioning regimens, including thiotepa, has been reported for primary CNS lymphoma (CNSL) and secondary CNSL. 40,[42][43][44][45][46][47][48][49][50] While there are reports of zero cases of TRM when conditioning regimens with thiotepa are administered in primary CNSL, when administered in secondary CNSL, all studies report TRM in a small proportion of patients. Therefore, the effectiveness of performing auto-PBSCT at CR1 with a conditioning regimen that includes thiotepa for patients considered highly likely to have CNS recurrence at the initial onset has not been clearly demonstrated, but there is also no guarantee of safety.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the usefulness of conditioning regimens, including thiotepa, has been reported for primary CNS lymphoma (CNSL) and secondary CNSL. 40,[42][43][44][45][46][47][48][49][50] While there are reports of zero cases of TRM when conditioning regimens with thiotepa are administered in primary CNSL, when administered in secondary CNSL, all studies report TRM in a small proportion of patients. Therefore, the effectiveness of performing auto-PBSCT at CR1 with a conditioning regimen that includes thiotepa for patients considered highly likely to have CNS recurrence at the initial onset has not been clearly demonstrated, but there is also no guarantee of safety.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose chemotherapy (HDC) with autologous stem cell transplantation (ASCT) has been investigated for post-remission consolidation and for relapsed disease, with promising results [ 11 , 12 , 24 , 25 , 26 , 27 , 28 ]. HD-MTX–based induction regimens, followed by ASCT, with various conditioning regimens, including BEAM (carmustine, etoposide, cytarabine, melphalan) [ 29 ], thiotepa, busulfan [ 30 , 31 ], TBC (thiotepa, busulfan, cyclophosphamide) [ 32 , 33 , 34 ] and thiotepa, carmustine [ 35 , 36 , 37 , 38 ] have been evaluated. The data thus far, however, have been limited to single-arm phase II-III trials, and several important questions remain, including the best candidates for such therapy, timing of its use, possible toxicities, and optimal conditioning regimen.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 48 central nervous system lymphoma (CNSL) patients, who have received high-dose chemotherapy and ASCT using a TBC (thiotepa, busulfan, cyclophosphamide) conditioning regimen, showed that the 2-year PFS and OS were 80.5% and 80.1%, respectively (75). The 2-year PFS and OS for patients with PCNSL in CR1 were 95.2% and 95.2%, respectively.…”
Section: Autologous Stem-cell Transplantation (Asct)mentioning
confidence: 99%